Transforming University of California, Irvine medical physiology instruction into the pandemic era - Lepe, Javier J. (FASEB Bioadv, 2020)
At the University of California, Irvine, School of Medicine (UCISOM), the COVID‐19 pandemic is accelerating the transition of face‐to‐face didactic lectures to online platforms. Institutions nationwide have opted to transition their lectures into remote instruction for the upcoming Fall 2020 academic year. UCISOM’s pre‐clerkship Medical Immunology course in the Spring 2020 serves as a template for other medical courses to successfully transform lecture content into virtual presentations. To help facilitate successful large‐scale transition to online courses, UCI developed institutional support and implemented a Division of Teaching Excellence and Innovation (DTEI) Fellowship and iMedEd programs to support medical educators throughout Summer. Previously developed E‐learning modules for renal and acid‐base physiology serve as the foundation for novel pulmonary E‐learning modules at UCISOM. In preparation for the new academic year, in a collaboration between faculty, UCISOM’s top performing second‐year medical students (MS2s) and DTEI fellows worked together during the summer to transition UCISOM’s Medical Physiology and Pathophysiology course online. With over 100 first‐year medical students attending the Medical Physiology course over live synchronous Zoom instruction, formative and summative assessments were incorporated into Canvas modules along with peer‐led review sessions and new E‐learning modules to educate and monitor student progress. The course will maintain existing in‐person active learning activities for students to get hands‐on experience using the latest medical devices while maintaining social distancing. Successful transition to online medical education at UCISOM will depend on increasing use of formative assessments, increased utilization of peer‐led review sessions, and efficient communication to help foster self‐directed learning.